USABILITY ENGINEERING ANALYSIS ON MY BEST E-LEARNING APPLICATION UNIVERSITY OF BINA SARANA INFORMATIKA - Hartati, Tri; Hikmah, Noer; Riyanto, Verry (Journal of Information System, Informatics and Computing, 2023)
After the Covid-19 pandemic ended, the lecture system at several universities in Indonesia began to gradually improve. The lecture system for several courses is carried out face-to-face. However, there are still several courses that are conducted online using e-learning applications with various considerations for the needs of the university. Bina Sarana Informatics University (UBSI) is a technology-based university where the learning system has implemented internet technology even long before the Covid-19 pandemic occurred. UBSI always strives to continue to improve the quality of the e-learning system that has been implemented. This can be seen from the development of e-learning applications for the lecture process which makes it easier for lecturers and students to access and absorb information related to campus academics. My Best is an e-learning application that is currently used in the KBM process in the UBSI environment and to improve the quality of the application used it is necessary to carry out a usability engineering evaluation. This analysis method consists of several stages, namely platform constraints, general design principles, conceptual model and screen design. The results of the usability analysis on the My Best e-learning application at Bina Sarana Informatika University have complete stage coverage, this means that My Best is an e-learning application in the very good category.